Impact of Modified Urban Surfaces on Enhancing the Microclimate of Residential Landscape Areas in Hot Arid Environments – Case Study of Jumeirah Village Circle Community, Dubai - Taheri, Farangis (2015)
The existing structure of the urban form with negligible greenery has created the urban heat islands (UHI) in many areas of the world. This can to an extent be reduced through thoughtful landscape design, which in turn influences the sustainability of urban fabric. The microclimate can be modified by the urban environment through certain techniques. The geographical situation and the arrangement of the metropolitan such as geometrical formation, morphology local climatology, human activities, vegetation, building and surface materials and water, contribute essential impacts on the urban microclimate. The aim of this study was to redesign the landscape surfaces of Dubai residential neighborhood based on bioclimatic interventions in order to achieve lower Mean Radiant and Ambient Air temperatures in hot arid climates. This paper, comprehensively investigated the effects of selected bioclimatic factors on the air temperature in order to improve residential outdoor spaces in Dubai. The Jumeirah Village Circle neighborhood was selected for the current study as an ideal spot due to its huge untreated spaces, building proximity, climatic factors, high demands and newly developed. The current situation of the site consists of absence of proper and adequate vegetation coverage, absence of water features or water bodies throughout the whole plot, presence of traditional asphalt roads and existence of many untreated spots covered with sandy soil. Primarily, in addition to the existing condition of the site four scenarios were proposed and examined to select the most useful ones in terms of passive cooling. The 5 longest summer day -21st of June- was the target of the variables including cool pavement, vegetation and water bodies. The five scenarios had a half day simulation consisting the part of the day when the sun appears between 6.00 AM and 6.00 PM to accomplish stability between the temperature behaviors during daytime and nighttime. The experimental outcomes of the simulations performed, displayed the behaviors of Ambient Air Temperature and Mean Radiant Temperature phenomena which were extracted from ENVI-met and justified. The results of the five scenarios compared to each other revealed that the integration of the bioclimatic criteria recommended, enhanced the Ambient Air Temperature by 0.44 K. In a logical sequence, the enhanced vegetation scenario recorded the second best performance after the combined scenario. Therefore, the vegetation demonstrated to be the most temperature reduction parameter followed by the cool pavement material and waterbodies respectively. This highlights the capability of the bio-climatically enhanced scenario to generate the lowest temperature values in the current investigation as predicted. Moreover, the findings confirmed that vegetation, water bodies and cool pavements are highly recommended as actual means for the enhancement of microclimatic conditions in outdoors in hot dry regions.